Biochar dari Biomassa Kusambi, Akasia, dan Kayu Putih sebagai Media Semai Benih Selada (Lactuca sativa L.) - Origenes Boy Kapitan; Anna Tefa; Dewi S. Hede; Filogus N. Payon (Savana Cendana, 2019)
Seedling media is one of the factors that influence seed germination. The requirements for seed germinating are media constituent material have a porosity for water retention and air circulation. One of the porous material that can be used as seedling media is biochar. Characteristic of biochar depend on the pyrolisis temperature and the type of biomass. This study aims to determine the percentage conversion of biomass from 3 types of woody biomass to biochar, the chemical characteristics of biochar resulting from pyrolysis at 3 different temperatures, viability of lettuce seeds on seedlings media with biochar, soil, and compost. This study used a factorial completely randomized design that was repeated 3 times. The first factor is the type of woody biomass which consists of 3 levels, namely lac tree, eucalyptus, and acacia. While the second factor is the pyrolisis temperature which consists of 3 temperature variations namely 350 oC, 450 oC, and 550 oC. The results showed that the higher percentage of biochar yield was produced on the type of lac tree with pyrolysis temperature at 350 oC. Biochar pH is alkaline except for biochar from lac tree with pyrolysis temperature at 350 oC. The highest EC value is produced by eucalyptus biochar with a pyrolysis temperature at 550 oC. The type of eucalyptus biochar has C-total, N, P, and K content greater than the other, while the largest CEC value is produced by the type of lac tree biochar. The best seed germination of lettuce is produced by eucalyptus biochar at pyrolysis temperature on 450 oC. Generally, the type of acacia wood biochar gives the best germination in all pyrolisis temperatures.